Analysis of Drought Evolution Characteristics in Haihe River Basin Based on Sub-Period Prediction Model - HAN Dongmei; JIANG Shanshan (Renmin Zhujiang)
In order to reduce the prediction uncertainty of future extreme climate events,a sub-period prediction model was constructed based on the daily observed precipitation data of 0.5°×0.5° provided by the China Meteorological Data Service Center and the simulated data of five global climate models (GCMs) from CMIP5.Meanwhile,the spatio-temporal evolution of drought in the Haihe River Basin (HRB) during 2020—2050 was predicted.Results show that both single GCM and multi-model ensemble average can better reproduce changes in annual average precipitation in HRB,but a large error in extreme precipitation simulation exists.The sub-period prediction model was constructed by the regression relationship at the monthly scale between the five GCMs and actually observed precipitation,and the test results show that the model has significantly improved the simulation ability of extreme precipitation in HRB.In the future,HRB tends to be humid,with moderate drought mainly appearing.Spatially,the frequency and degree of drought increase from west to east.This study aims to provide a reference for improving the ability of GCMs in simulating extreme climate events and offer ideas for decision-making for future droughts in HRB.